Generazione Erasmus? L'identità europea tra vissuto e istituzioni - Bettin Lattes, Gianfranco; BONTEMPI, MARCO (Strumenti per la didattica e la ricerca, 2008)
The Erasmus programme is one of the outstanding Community initiatives, even if it is spoken little of outside the world of the university. This book, one of the first devoted to the subject, analyses the virtuous effects that the programme has had on the university system, the geography of student flows, and the motivations and propositions of those who have taken part in it. The reports of the students indicate the Erasmus as a 'bubble of experience' and the book explores these inner experiences through a sociological approach, illustrating the vast potential in terms of the moulding of a 'homo novus Europaeus'. The data gathered prompt a reflection on the redefinition of the role of the student when he or she directly experiences the comparison with a context different and distant from that of origin, to which he or she is nevertheless destined to return. From this perspective, the Erasmus experience assumes the significance of a sort of temporary upheaval of status open to forms of 'experimentation of identity'.